Altered coordination strategies during upright stance and gait in teachers of the Alexander Technique - Johnson, Molly B.; Cohen, Rajal G. (Frontiers in Aging, 2023)
Deterioration in movement and posture often occur with aging. Yet there may be approaches to movement training that can maintain posture and movement coordination patterns as we age. The Alexander Technique is a non-exercise-based approach that aims to improve everyday movement and posture by increasing awareness and modulating whole-body postural muscle activity. This study assessed whether older Alexander Technique teachers showed different posture and movement coordination patterns than age-matched controls during upright stance and gait using 3D inertial sensors. During upright stance, Alexander Technique teachers showed lower centroidal sway frequency at the ankle and lower normalized jerk at the sternum than controls. During gait, Alexander Technique teachers had more symmetrical gait cycles, more symmetrical arm swing velocity, greater arm swing velocity, greater arm swing range of motion, and lower range of acceleration of the torso in the frontal plane than controls. Smoother control of upright posture, more stable torso motion, and less restrained arm mobility suggest that Alexander Technique may counter movement degradation that is found with aging. Results highlight the important balance between mobility and stability within the torso and limbs.